Facial Rejuvenation Enhancing Cheek Lift - Bellity, Philippe (Arch Plast Surg, 2017)
Supported by recent literature on the signs of aging of the middle and lower face, our clinical research has documented a loss of volume of the deep structural components of the central face and a progressive descent of the nasolabial fat and the jowl fat, leading to facial fragmentation. The signs that appear around the age of 45 to 50 years are well targeted by the mini-invasive technique described here. We focused on refitting the jowl fat and the nasolabial fat associated with cutaneous tightening. The use of absorbable barbed sutures (Quill) led to significant improvements, enabling the fitting of fat on fat. In the past 4 years, 167 operations were performed using this technique. The clinical results were very satisfactory, yielding a natural effect caused by the mobilization and strong fixation of the nasolabial fat and the jowl fat in the direction opposite to their displacement.